1997
DOI: 10.1042/bj3220867
|View full text |Cite
|
Sign up to set email alerts
|

Structure and organization of amplicons containing the E4 esterase genes responsible for insecticide resistance in the aphid Myzus persicae (Sulzer)

Abstract: Insecticide resistance in the aphid Myzus persicae results primarily from the amplification of genes encoding the insecticidedetoxifying esterase, E4. Here we report the analysis of flanking DNA co-amplified with the E4 gene. The 5h end of this gene has an untranslated leader sequence interspersed by two introns, and the promoter region lacks TATA and CAAT boxes. The DNA breakpoint involved in the generation of the amplification is just upstream (approx. 250 bp) of the putative E4 transcription start site ; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 30 publications
1
37
0
1
Order By: Relevance
“…Massive amplification of the EPSPS gene randomly dispersed throughout the genome (Gaines et al, 2010), likely mediated by transposable elements (Gaines et al, 2013), has been recently reported in GR A. palmeri. Tandem amplifications of genes that metabolize insecticides have been reported in organophosphate-resistant populations of Culex quinquefasciatus mosquitoes (Paton et al, 2000) and Myzus persicae (Field and Devonshire, 1997). Our results demonstrate the tandem amplification of a target gene itself as a basis for mechanism of herbicide resistance.…”
Section: Discussionmentioning
confidence: 58%
“…Massive amplification of the EPSPS gene randomly dispersed throughout the genome (Gaines et al, 2010), likely mediated by transposable elements (Gaines et al, 2013), has been recently reported in GR A. palmeri. Tandem amplifications of genes that metabolize insecticides have been reported in organophosphate-resistant populations of Culex quinquefasciatus mosquitoes (Paton et al, 2000) and Myzus persicae (Field and Devonshire, 1997). Our results demonstrate the tandem amplification of a target gene itself as a basis for mechanism of herbicide resistance.…”
Section: Discussionmentioning
confidence: 58%
“…In Myzus persicae, ampli®ed esterase gene copy number can also vary. There is evidence to show that¯uctuations in the copy number of this gene which is integrated into the chromosome are related to unequal sister chromatid exchange (Field & Devonshire, 1997). Despite the dierences in ampli®cation level between the strains, the RFLP data were identical.…”
Section: Levels Of Ampli®cationmentioning
confidence: 95%
“…Large tandem gene amplifications of metabolic genes confer insecticide resistance in Culex mosquitoes and Myzus aphids (36,37). Organophosphate-resistant mosquitoes had ≈80-fold more copies of esterase genes than susceptible mosquitoes (37).…”
Section: Discussionmentioning
confidence: 99%